2022
DOI: 10.3389/fimmu.2022.1001320
|View full text |Cite
|
Sign up to set email alerts
|

An immunogenic cell death-related regulators classification patterns and immune microenvironment infiltration characterization in intracranial aneurysm based on machine learning

Abstract: BackgroundImmunogenic Cell Death (ICD) is a novel way to regulate cell death and can sufficiently activate adaptive immune responses. Its role in immunity is still emerging. However, the involvement of ICD in Intracranial Aneurysms (IA) remains unclear. This study aimed to identify biomarkers associated with ICDs and determine the relationship between them and the immune microenvironment during the onset and progression of IAMethodsThe IA gene expression profiles were obtained from the Gene Expression Omnibus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The cancer cells undergoing ICD could expel HMGB1 from nucleus outside the cells (Gao et al., 2022 ; Turhon et al., 2022 ). The expression level of HMGB1 on MCF-7/ADR cells was conducted by immunofluorescence assay.…”
Section: Resultsmentioning
confidence: 99%
“…The cancer cells undergoing ICD could expel HMGB1 from nucleus outside the cells (Gao et al., 2022 ; Turhon et al., 2022 ). The expression level of HMGB1 on MCF-7/ADR cells was conducted by immunofluorescence assay.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, the mechanisms of m6A methylation [49] and immunogenic cell death [50] in IAs were also investigated. In the future, further investigation should be conducted on the mechanism of its role in IAs in DNA methylation and more epigenetic regulation.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, advancements in genetic technologies and bioinformatics, including gene expression profiling and protein–protein interaction analyses, 5,6 have been supplemented by robust machine learning techniques to identify key gene expressions in intracranial aneurysms 7,8 . A recent study by Alejandra et al reported a comprehensive analysis of gene heterogeneity by single‐cell RNA sequencing in healthy as well as atheromatous mice 9 .…”
Section: Introductionmentioning
confidence: 99%